Motivational Dynamics - Pay Scale and Its Bearing on Employee Job Satisfaction: A Comparative Study Between India and Malaysia - Thakuria, Radharani (2009)
This paper constitutes a synopsis of the interplay between diverse variables in an organizational setting, that crucially directs the levels of satisfaction and the consequent productivity of all employees in general and that in Hindustan Unilever Limited (HUL), India and Hewlett Packard(HP), Malaysia in particular. The basic objective of this research is to find out what promotes employee satisfaction and how can it be sustained in an organization through the medium of monetary and non monetary incentives. A comparative study is undertaken in the background of the cultural differences between India and Malaysia to gauge whether employees across geographical borders hold the same notion as regards the importance of monetary and non monetary rewards in promoting job satisfaction of the employees or is their perception affected by the cultural differences. A Qualitative study is conducted based on Interviewing and Grounded Theory which led to the insightful finding that though pay is significant as a motivator, it is the balance between pay and non monetary rewards that can promote employee satisfaction through preservation of the psychological contract. Knowing what category of reward to emphasize on depending upon situations, management can contribute towards upgrading the levels of employee motivation extracting higher productivity and greater commitment from them in the long run. The might of this ideal combination even transcends the cultural impact on individuals eliciting this unanimous opinion from employees of any origin.